Trends in teenage pregnancy in Brazil in the last 20 years (2000-2019) - Monteiro,Denise Leite Maia (2021)
SUMMARY OBJECTIVE: The aim of this study was to evaluate the frequency of teenage pregnancy in all Brazilian regions and states in the period of 2000-2019 among two age groups, namely, 10-14 and 15-19 years old, and correlate it with the human development index. METHODS: A cross-sectional study was performed by using the data from the Live Birth Info System from the National Health System’s database. RESULTS: The percentage of live births from teenage mothers (age 10-19 years) in Brazil decreased by 37.2% (i.e., 23.4 in 2000 to 14.7% in 2019) in all regions. Amazonas and Maranhão were the only states to show increased fertility rates for teens in the age group of 10-14 years. The fertility index decreased from 80.9-48% in all states among mothers aged 15-19 years. Only the Southeast and South regions showed levels below the Brazilian average (i.e., 38.2 and 39%, respectively). The proportion of live birth showed an inversely proportional trend to the human development index score. CONCLUSIONS: Brazil shows a decline in the percentage of live birth among adolescent mothers and the fertility rate. Live birth is inversely proportional to the human development index score. However, the teenage pregnancy numbers are still high, with great regional inequality in the country.